Analysis of Local Chicken Entreprise in DAS Serayu Banyumas - Hidayat, N Noor; Soeprapto, Soeprapto (ANIMAL PRODUCTION, 2000)
The Objectives of this research was to know income and efficiency level of local chicken entreprise. Beside that, to know potency of local chicken enterprise developing in DAS Serayu, Banyumas and know factors can effect level of that income and efficiency. Methode that used at this research is survey method to farmer families. Take of research data by random sampling.The data is analysed by multiple regression analysis. The results of this research showed that income level of local chicken entreprise at DAS Serayu is Rp 277.375,00 / year and economi efficiency 2.80 , that means the farmers get return Rp 2.80 for every one unit cost addition. The age of farmers and total of chicken possession effect at efficiency of Â local chicken entreprise. Potency of local chicken developing very big if showed from power of area and human resources. Very important to increase entreprise capital and increase knowledge for farmer. Beside that more important present motivation and support for develop there enterprise (Animal Production 2(1): 13-17 (2000)Key Words: local chicken, farmers income, economic efficiency